Source code and data for the PhD Thesis "Learning neural graph representations in non-Euclidean geometries" - López, Federico (Universität, 2023)
This dataset contains source code and data used in the PhD thesis "Learning Neural Graph Representations in Non-Euclidean Geometries". The dataset ...